The answer is 64.4 because you multiply 92 times 0.7 and get 64.4
Answer:
The fourth term of the expansion is -220 * x^9 * y^3
Step-by-step explanation:
Question:
Find the fourth term in (x-y)^12
Solution:
Notation: "n choose k", or combination of k objects from n objects,
C(n,k) = n! / ( k! (n-k)! )
For example, C(12,4) = 12! / (4! 8!) = 495
Using the binomial expansion formula
(a+b)^n
= C(n,0)a^n + C(n,1)a^(n-1)b + C(n,2)a^(n-2)b^2 + C(n,3)a^(n-3)b^3 + C(n,4)a^(n-4)b^4 +....+C(n,n)b^n
For (x-y)^12, n=12, k=3, a=x, b=-y, and the fourth term is
C(n,3)a^(n-3)b^3
=C(12,3) * x^(12-3) * (-y)^(3)
= 220*x^9*(-y)^3
= -220 * x^9 * y^3
Answer:
Step-by-step explanation:
Let the numbers be x and y.
<u>The equations are:</u>
<u>Add up the equations to eliminate y and solve for x:</u>
- x - y + 2x + y = 2 + 13
- 3x = 15
- x = 15/3
- x = 5
<u>Now find the value of y:</u>
- y = x - 2
- y = 5 - 2
- y = 3
Answer:
thanks hi are you squid game girl which to
Answer:
a) PR = 17 cm, b) QR = 6 cm
Step-by-step explanation:
∠Q=90, so PQ and QR are legs, and PR is hypotenuse.
Pythagorean theorem PQ² + QR² = PR²
a) PQ² + QR² = PR²
8² + 15² = PR²
PR² = 289
PR = 17 cm
b) PQ² + QR² = PR²
8² + QR² = 10²
64 + QR² = 100
QR² = 36
QR = 6 cm